Fabrication, Characterization and Biological Evaluation of PRGD/PDLLA/β-TCP Scaffold for Nerve Regeneration (Journal of Fiber Bioengineering and Informatics, 2015)
A novel nerve repairing material PRGD/PDLLA/\u03b2-TCP was synthesized and characterized with\rScanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR) spectroscopy, and mass loss\rratio. The effects of PDLLA or PRGD/PDLLA/\u03b2-TCP on viability and growth of Schwann Cells\r(SCs) were investigated by MTT assay and SEM. After implantation of different materials, histological\rassessment was performed. The results showed that, compared with PDLLA, PRGD/PDLLA/\u03b2-TCP\rmaterials displayed better biocompatibility, degradation property and less inflammatory reaction.\rMoreover, PRGD/PDLLA/\u03b2-TCP materials promoted the adhesion and proliferation of Schwann cells\rand exhibited better degradation performance than pure PDLLA. These results indicated that PRGD/\rPDLLA/\u03b2-TCP has a potential application in the fields of nerve regeneration.